2018
DOI: 10.7897/2230-8407.097148
|View full text |Cite
|
Sign up to set email alerts
|

A NOVEL STABILITY-INDICATING RP-UPLC METHOD FOR THE QUANTIFICATION OF IMPURITIES AND A NEW QDa MASS DETECTOR COUPLED WITH LC-PDA FOR IDENTIFICATION OF MASS OF DEGRADATION PRODUCTS IN A FIXED DOSE COMBINATION OF EMPAGLIFLOZIN AND LANIGLIPTIN TABLETS USED AS SECOND-LINE THERAPY FOR TYPE-2 DIABETES

Abstract: A new UPLC method was developed for identification and quantification of process related impurities and degradation products in a new fixed dose combination product of empagliflozin and linagliptin tablets, which is used to treat type-2 diabetes. Chromatographic separation was obtained using a new phenomenex Luna omega polar C18, 100x2.1mm, 1.6µ and a gradient programme consisting of Mobile phase A: 10mM Potassium dihydrogen orthophosphate pH-3.0 and Mobile phase B: acetonitrile and methanol (55:45%v/v). Degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to the literature review it was found that, many analytical techniques have been reported for the determination of EMP and LIN, including UV spectrophotometry (Amrutiya et al, 2017;Ayoub, 2016;Cholke et al, 2019;Padmaja & Veerabhadram, 2015), voltammetry (Naccar, Saleh, Omar, Haredy, & Derayea, 2020), HPTLC (Bhole, Wankhede, & Pandey, 2017;Thakor, Amrutkar, & Chaudhari, 2019), HPLC (Abdel-Ghany, Ayad, & Tadros, 2018Al-Sabti & Harbali, 2020;Attimarad, Nagaraja, Aldhubaib, Nair, & Venugopala, 2014;Basak, Gouru, Bera, & Nagappan, 2019;Donepudi & Achanta, 2018;El-Bagary, Elkady, & Ayoub, 2013;Ganorkar, Askarkar, Gupta, & Milind, 2020;Geetha Swarupa, Lakshmana Rao, Prasad, & Suresh Babu, 2016;Gholami, Bahrami, & Faraji, 2020;Manoel et al, 2020;Naazneen & Sridevi, 2016;Padmaja & Veerabhadram, 2017;Rajbangshi, Alam, Hossain, Islam, & Rouf, 2018;Salapaka et al, 2019;Sharif et al, 2020;Supriya Reddy, Chandan, Sai Charan, & Akshay, 2020;Vemula, Dodda, Balekari, Panga, & Veeresham, 2015;Wattamwar, Mungantiwar, Halde, & Pandita, 2020;Yadav, Dornala, Swain, Prabha, & Samanthula, 2020), UPLC (Ayoub, 2015;Dubey, Singh, Tyagi, Bhardwaj, & Raghav, 2014;Jagadabi, Kumar, Pamidi, Ramaprasad, & Nagaraju, 2018;Madana Gopal & Sridhar, 2017;Nannapaneni, Jalalpure, Muppavarapu, & Sirigiri, 2016)…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review it was found that, many analytical techniques have been reported for the determination of EMP and LIN, including UV spectrophotometry (Amrutiya et al, 2017;Ayoub, 2016;Cholke et al, 2019;Padmaja & Veerabhadram, 2015), voltammetry (Naccar, Saleh, Omar, Haredy, & Derayea, 2020), HPTLC (Bhole, Wankhede, & Pandey, 2017;Thakor, Amrutkar, & Chaudhari, 2019), HPLC (Abdel-Ghany, Ayad, & Tadros, 2018Al-Sabti & Harbali, 2020;Attimarad, Nagaraja, Aldhubaib, Nair, & Venugopala, 2014;Basak, Gouru, Bera, & Nagappan, 2019;Donepudi & Achanta, 2018;El-Bagary, Elkady, & Ayoub, 2013;Ganorkar, Askarkar, Gupta, & Milind, 2020;Geetha Swarupa, Lakshmana Rao, Prasad, & Suresh Babu, 2016;Gholami, Bahrami, & Faraji, 2020;Manoel et al, 2020;Naazneen & Sridevi, 2016;Padmaja & Veerabhadram, 2017;Rajbangshi, Alam, Hossain, Islam, & Rouf, 2018;Salapaka et al, 2019;Sharif et al, 2020;Supriya Reddy, Chandan, Sai Charan, & Akshay, 2020;Vemula, Dodda, Balekari, Panga, & Veeresham, 2015;Wattamwar, Mungantiwar, Halde, & Pandita, 2020;Yadav, Dornala, Swain, Prabha, & Samanthula, 2020), UPLC (Ayoub, 2015;Dubey, Singh, Tyagi, Bhardwaj, & Raghav, 2014;Jagadabi, Kumar, Pamidi, Ramaprasad, & Nagaraju, 2018;Madana Gopal & Sridhar, 2017;Nannapaneni, Jalalpure, Muppavarapu, & Sirigiri, 2016)…”
Section: Introductionmentioning
confidence: 99%